Increasing Student Learning Motivation in Sociology Learning Through Digital Technology: A Qualitative Study at SMAS Muhammadiyah 8 Kisaran Asahan - Jannah, Nadhirotul; Dora, Nuriza (Yayasan Sembilan Pemuda Indonesia, 2025)
This research examines the application of digital technology to enhance students’ learning motivation in Sociology subjects in the 10th grade at SMAS Muhammadiyah 8 Kisaran. The background of the study is based on the fact that learning is still dominated by conventional methods, while today’s learners are a digital generation that requires a more interactive and contextual approach to learning. This research uses a qualitative approach with descriptive methods. Data were collected through in-depth interviews with teachers and students, as well as observations during the learning process. The research results show that the use of digital media such as Quizizz and Wordwall can significantly enhance students’ attention, active participation, and learning motivation. Students showed positive responses as learning felt more enjoyable and competitive. However, there are challenges such as limited internet access and teacher readiness. Technology integration has proven to be effective in supporting learning that aligns with the characteristics of Generation Z. Therefore, the use of digital media is recommended as an innovative strategy in Sociology education.